Determining Strategic Locations for MSMEs in Sario District Using SAW Ranking with AHP Weighting - Rillya Arundaa; Winsy Ch. D. Weku; Sri Yunda Giasi (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an essential role in the Indonesian economy due to their significant contribution to national economic growth as well as their ability to create jobs for local communities. The long-term success of MSMEs is not only determined by the products or services they offer, but also by the strategic business locations they select. However, identifying strategic locations is challenging due to the lack of structured tools, objective evaluation of multiple criteria, and limited use of integrated decision-support models. This research aims to determine the most strategic location for the development of MSMEs in Sario District, Manado City, by considering several key factors, including accessibility, population density, rental costs, community income levels, and infrastructure availability. These issues highlight the need for a systematic and objective approach to support decision-making in location selection. The problem faced in determining the location is the difficulty of integrating all criteria objectively and systematically. For this reason, the Analytical Hierarchy Process (AHP) method is employed to determine the weight of each criterion. In contrast, the Simple Additive Weighting (SAW) method is utilized to rank the alternative locations. The analysis found Sario Tumpaan (A4) as the most strategic location and Sario (A3) as the least. Data were obtained from surveys, interviews, questionnaires, and agency documents. The AHP–SAW-based Decision Support System effectively provided objective and consistent recommendations, with Sario Tumpaan serving as a benchmark for future evaluations and development.